La Prensa como Actor Colectivo en La Transición Española a La Democracia. El Ejemplo de Los Dos Editoriales Conjuntos de 1977 - Zugasti Azagra, Ricardo (Re-presentaciones: Periodismo, comunicación y sociedad, 2008)
During the political transition to democracy after Franco’s death, the most relevant Spanish news- papers published two shared editorial articles in response to two events which threatened a peaceful path to à democratic regime for Spain. The first shared editorial was published within the context of the so-called "bloody week" in January 1977. Numerous terrorist attacks were committed by extremist groups during this week, putting at risk the stability of the democratic process. The second editorial was published in response to the reaction of the Army after the legalization of the Spanish Communist Party. Both shared editorial articles constitute an example of the role that the Spanish press played during the transition to democracy.